HUBUNGAN PERILAKU CARING PERAWAT DENGAN KECEMASAN PASIEN DI RUANG RAWAT INAP RSUD KABUPATEN BEKASI - Anindita Putri Suwarno (2022)
Someone who is in the treatment period or before the action is taken, often feels anxious and afraid of what will happen next to the patient, so nurses play an important role in overcoming patient anxiety because nurses apply caring behavior in nursing care and are one of the closest people to patients, and what patients always need to meet their needs during the treatment period. This study was conducted with the aim of analyzing the relationship between nurse caring behavior and patient anxiety in the inpatient room at the Bekasi District Hospital. This study used a cross-sectional research design with a sample of 217 hospitalized patients using the Quota Sampling method. Data were collected using two questionnaires modified by the researcher, namely the caring questionnaire with the Caring Behavior Assessment Tool (CBAT) and the patient anxiety questionnaire with the Hamilton Anxiety Rating Scale (HARS). The results of the bivariate analysis showed a p value of 0.062 (p > 0.05), so it can be concluded that there is no significant relationship between nurse caring behavior and patient anxiety in the inpatient room at the Bekasi District Hospital. It is recommended for hospital management to provide evaluation sheets through criticizing patient suggestions for hospital services, especially nursing services, and being able to increase knowledge for all nurses by holding seminars and training.